Solutions for Managing Wastewater in Florida Tomato Packinghouses - Gurpal Toor; Maninder Chahal; Bielinski Santos (EDIS)
A large amount of wastewater is produced in Florida's packinghouses during the cleaning and sanitizing of tomatoes. High transportation costs for off-site disposal and strict surface water discharge regulations are critical issues associated with the management of this wastewater. This 4-page fact sheet provides solutions for increasing the reuse of wastewater in tomato packinghouses in Florida. Written by Gurpal Toor, Maninder Chahal, and Bielinski Santos, and published by the UF Department of Soil and Water Science, August 2012.